EDUCATION VERSUS EXPERIENCE: WHICH MATTERS MORE FOR INDONESIAN BANK DIRECTORS? - Pangestu, Stevanus (Jurnal Manajemen, 2016)
The purpose of this paper is to assess the effects of board of directors’ education and experience on firmfinancial performance. Based on the cross-sectional analysis of 30 publicly-listed Indonesian banks, it isfound that both directors’ education and experience positively influence bank profitability, measured withReturn on Assets ratio. The results of this study support Hambrick and Mason’s Upper-Echelon theory.Based on the research findings, Indonesian banks are recommended to take experience and education intoaccount when organizing board members—with more emphasis on the former due to the moresignificantimpact it has. Furthermore, banks should also be encouraged to invest more in their human capital byfacilitating further education of their board members.